(3HdhZ GdCQH HQaY GdWdHs - (3eMeO GdHQdSj GdSYOj GdQTjOjs
(3ChdgG (B:s
(3hHYO adeG QCjJ eG hbY HGdOjGQ GdeUQjI ai gPG GdYGe (B(977) (3ef GdCehQ GdLSGe hGdBghGd GdYXGe , GbJVi GdMGd JYdjb Pdc bUOkG ddGYJHGQ s
(3BNQgG (B:s
(3dGjajO GdYdhe hGdeYQaI aGFOI dgeSWhGJ GdbgQ hYOe GdJhajb aCKHJge ai ehGWf GdYLR s
(3GdHQdSi NGOe GdTQjYI HGdGScfOQjI hOejGW hQTjOs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B50 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs